Participation in Prenatal Education, Knowledge and Attitude related to Delivery, Postpartum Care, Newborn Care in Nulliparous Women - Mi Young Kim; Gwang Suk Kim; Sue Kim; Hye Jung Lee (Korean Society of Women Health Nursing, 2016)
PURPOSE: This study was done to identify content of prenatal education and to examine differences in prenatal education, knowledge, and attitude of nulliparous South Korean women. METHODS: A cross-sectional survey design was used with 134 conveniently recruited nulliparous women. Data were collected through self-report questionnaires. RESULTS: Average number of institutional prenatal education programs was 5.96 at clinics, 4.31 at health care centers, and 0.49 at hospitals. Women participated in an average 5.78 out of the 35 prenatal education contents: 15 types of prenatal and delivery, 10 postpartum self-care, and 10 parenting. Score for knowledge was 7.57out of 10. Women who participated in prenatal education (n=72) reported significantly higher scores in knowledge (t=2.71, p=.008) than women who did not participate (n=62). The average score for attitude was 7.22 out of 10. Nulliparous women over 36 weeks of gestational age had significantly higher scores for attitude (t=2.38, p=.019) than women under 36 weeks. There were significant positive correlations between newborn care knowledge and postpartum care self-efficacy (r=.26, p=.026), and newborn care knowledge and parenting confidence (r=.25, p=.034). CONCLUSION: Results indicate that policy is needed to increase participation in prenatal education and to establish strategies for health care centers and hospitals to provide prenatal education.